KEBIJAKAN PENCEGAHAN DALAM KEKERASAN SEKSUAL DI LINGKUNGAN PENDIDIKAN - Adityo Saputra; Ade Adhari (Fakultas Hukum Universitas Tarumanagara, 2021)
Rise of sexual violence against children, especially in the educational environment, makes parents feel that the educational environment has become an unsafe place for students. Because sexual violence will have a traumatic impact on both children and adults. Seeing the consequences that will be experienced by children when they become victims of sexual violence is very woorrying, therefore there is a legal protection given to victims, namely children who experience sexual violence.